The crucial role of nociceptin opioid peptide (NOP) receptor in attenuating relapse to morphine/methamphetamine (poly-drug) addiction in mice - Ridzwan, Irna Elina; Abdul Rahman, Nor Akhi Hijriyati; Wasli, Nur Syafinaz (A and V Publication, 2017)
A combination of buprenorphine/naltrexone treatment had been proven to successfully attenuate relapse (reinstatement) to morphine/methamphetamine (poly-drug) addiction in mice using a conditioned place preference (CPP) model. This treatment combination exhibits a mixed opioid receptor pharmacological activities (mu/kappa antagonist and partial NOP agonist). Thus, this recent study aimed to investigate the independent role of the NOP receptor in attenuating relapse to this poly-drug addiction. The male Swiss albino mice were made dependent on 7.5 mg/kg morphine/1.0 mg/kg methamphetamine (poly-drug). The mice were injected with SB 612111 (a selective NOP antagonist) during reinstatement phase, 30 minutes before the administration of0.3 mg/kg buprenorphine/1.0 mg/kg naltrexone combination. The priming dose of poly-drug (2.5 mg/kg morphine/1.0 mg/kg methamphetamine) were given 10 minutes later. The percentage of time spent at the drug-paired compartment was compared with the control group (did not receive SB 612111 treatment). The results revealed that the relapse to poly-drug addiction happened in the group of mice that received SB 612111 prior to buprenorphine/naltrexone (53.81 ± 11.23 %, n = 6). This result was significantly different compared to its own baseline (before the mice were made dependent on poly-drug [-5.37 ± 6.42 %, n = 9, p < 0.05]). In contrast, relapse was significantly attenuated (reduced) in the group of mice that did not receive SB 612111 prior to buprenorphine/naltrexone (19.14 ± 16.89 %, n = 5). The percentage of time spent at the drug-paired compartment was found to be not significantly different compared to its own baseline (-16.14 ± 4.81 %, n = 13). The result suggests that an agonist activity at the NOP receptor is crucial in attenuating relapse to morphine/methamphetamine (poly-drug) addiction. Hence, further investigation needs to be done to evaluate the involvement of this receptor at the brain level.